Arabic Speech Act: Investigating Students' Pragmalinguistic Competence in Requesting and Apologizing Expressions - Abdul Muid; Anwar Sanusi; Sulhi Muhammad Daud Abdul Kadir (An Nabighoh Jurnal Pendidikan Dan Pembelajaran Bahasa Arab, 2024)
This study aimed to determine the speech act strategies of requesting and apologizing sentences in Arabic produced by Non-Native Speakers (NNS). This study used a qualitative approach with a case study design. Participants in this study were 50 students of the Arabic Language Education Study Program at Jambi University. The results of this study suggest that the most dominant request strategy is conventionally indirect (60%), especially the query preparatory sub-strategy, which is used to maintain politeness by asking questions without the impression of forcing. In addition, the direct strategy with the sub-strategy of the derivable mood (imperative) is also used, although with a lower frequency, with polite expressions such as "min faḍlika" to maintain politeness. Non-conventionally indirect strategies (5%) were also found, where speakers gave indirect hints to convey requests subtly. The apology strategy was the most frequently used (68%), followed by acknowledgment of responsibility (20%) and promise of non-recurrence (10%). The explanation or account strategy was used at a shallow frequency (2%).